Sosialisasi dan Bakti Sosial Covid-19 di Kelurahan Sepinggan Raya Balikpapan - Maslina Maslina; Isradi Zainal; Andi Surayya Mappangile (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2020)
Covid19 socialization and social serviceactivities are community service activities in an effort to help people filfill their life needs and solve the community problems by especially indealing withCOVID19 transmission activities are carried out through the Covid19 socialization and social service program which is a communityservice-based activity to increase public knowledge concerning effort to break the chain of Covid19 transmission carried out in RT 2, 3 and 4 of Sepinggan Raya District, Balikpapan City with service methods in the form of counseling activities, demonstrations, distribution of masks and basic necessities and spraying Disenfektan in residential areas. The results showed a positive response from the government and active participation of community.